ANALYSIS OF THE INFLUENCE OF THE EXTERNAL ENVIRONMENT FACTORS ON THE ENTERPRISES COMPETITIVENESS FORMATION - GUOHE, Qin (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In today's conditions of instability of the economic situation, accounting for the impact of the region's entrepreneurial climate is necessary for the formation of a successful strategy for increasing the enterprise's competitiveness. The conditions for effective entrepreneurial activity are different in different regions. To take this circumstance into account, it is necessary to clearly define the composition of the elements of the regional environment (subjective factors) and the institutional environment (objective factor), which affect the level of competitiveness of regional enterprises. The entrepreneurial climate is the basis of the company's competitiveness. The more it contributes to entrepreneurial activity, the more competitive the enterprise will be. The factors of the region's entrepreneurial climate significantly affect the process of formation and preservation of competitive advantages of the enterprise. The competitiveness of an enterprise is a multifactor value. In the long term, in the conditions of a free market and competitive relations of its participants, it will be determined by combinations of various factors. The competitiveness of products (works, services) is obviously the central element of the formation of the enterprise's competitiveness, the level of which the enterprise's competitiveness cannot be fixed in the zone of positive values. Successful sale of products ensures income generation and financial results, creating conditions for formation and maneuvering of financial funds. Without it, neither current nor prospective functioning of the organization is possible. It is necessary to consider the enterprise's competitiveness both from the standpoint of the presence of competitive advantages today, and from the standpoint of the possibility of maintaining or possible use of competitive advantages in the future due to changes in the market situation (in the industry). This circumstance makes it possible to reasonably determine the competitiveness of the enterprise not as a discrete value that characterizes the enterprise's position on the market (in the industry) at a particular moment in time, but as a complex characteristic of the enterprise's ability to respond to changes in the market situation and use these changes to create competitive advantages.
Keywords: competitiveness; factors; external environment; enterprises; market conditions